Postrzeganie dzietności rodziny na podstawie badań porównawczych z 2013 i 2021. Wskazania dla katolickiego duszpasterstwa rodzin - Gorbaniuk, Julia; Szyszka, Małgorzata; Goleń, Jacek (Verbum Vitae, 2022)
The size of the family is one of the aspects differentiating its perception. This article addresses the issue of the perception of "small" and "large" families by various age groups in the context of Catholic family ministry. The analyses are based on the author’s own research from 2013 and 2021 conducted among 506 respondents, grouped into three categories according to age. The analysis focused on showing the differences in, and changes in, how individuals defined small and large families, and their perceptions of these types of families. Included is a discussion of the terminology employed and the demographic variables of the research sample. The analysis of empirical data showed a change in the definition of families. According to the respondents, a "small" family is a family with two children, and a "large" family – one with four children. Instead, the changes in the perception of families show a more diverse picture of a large family, and the novelty is drawing the respondents’ attention to the health possibilities of conceiving a child, which determine the size of the family. The article ends with conclusions and guidelines for the pastoral care of the family to strengthen respect for human life.